Patents. - Klee, M.M (IEEE Engineering in medicine and biology magazine)
Should a brand-name drug manufacturer be able to extend the life of its patent exclusivity by getting a patent on a compound that the body makes from one of its drugs? That was the question before the Court of Appeals for the Federal Circuit (CAFQ) in the recent case of Schering v. Geneva. To provide an answer, the court had to delve into the challenging question of inherent, as opposed to explicit, disclosures. The case involved the highly successful antihistamine drug, Claritin, and pitted Schering, the discoverer of the drug, against a raft of generic drug manufacturers who wanted to market generic Claritin.